Modification and control of topological insulator surface states using surface disorder - Sacksteder, Vincent (2018)
We numerically demonstrate a practical means of systematically controlling topological transport on the surface of a three-dimensional topological insulator, by introducing strong disorder in a layer of depth d extending inward from the surface of the topological insulator. The dependence on d of the density of states, conductance, scattering time, scattering length, diffusion constant, and mean Fermi velocity are investigated. The proposed control via disorder depth d requires that the disorder strength be near the large value which is necessary to drive the topological insulator into the nontopological phase. If d is patterned using masks, gates, ion implantation, etc., then integrated circuits may be fabricated. This technique will be useful for experiments and for device engineering.